Assembly and maturation of calf gut microbiome from neonate to post-puberty - Hyun Sik Kim; Jae-Yun Lee; Tae Woong Whon; Jin-Woo Bae (Scientific Data)
Abstract With the help of rumen bacteria, ruminants can feed on indigestible plant materials and produce over 70% of their energy as fatty acids. However, during lactation, ruminants exhibit characteristics of monogastric animals due to an undeveloped rumen; therefore, understanding gut microbiome changes in growing calves is essential. Our understanding of the gut microbiome in growing calves remains limited in large populations with the same diet, breed, and period. Here, we describe 16S rRNA gene amplicon sequencing data from 420 faecal samples, 20 rumen contents, 17 small intestine contents, and 18 large intestine contents collected from 57 healthy, antibiotic-free Korean beef cattle from neonatal to post-pubertal age. Eight 16S rRNA gene amplicon datasets from the host diet samples were obtained. Approximately 148 million raw reads, averaging 153,352 ± 96,050 (mean ± SD) reads per sample, and 51,596 unique amplicon sequence variants (381–368 per sample) were identified in the 483 samples. These shareable datasets can be reused by researchers to assess gut microbiome-related functions in growing calves and improve ruminant production and health.